REACTIONS OF THE CARDIAC FREQUENCY IN THE TRAINING OF "MUSIC FACTORY FOR BODY" CIRCUIT. (Fiep Bulletin - online, 2014)
The systemized programs of physical activity come growing and taking place in the market of fitness with great marketing, taking time of professionals and pupils, but little efficient with its results. The Music Factory for the Body circuit used as a study object in the research is characterized as "circuit for time", because the exercises are made with definite time and mixing aerobic and anaerobic exercises, without the control of training variables, selling an efficient image talking about the fat consumption during the training session. The idea of the research came from the doubt in the aerobic effectiveness, thus with the goal of verifying the behavior of the cardiac frequency during the circuit. The circuit was prepared from the following exercises: rowed low, extensor chair, supino inclined, flexor chair, flexion and extension of elbows in cross over, leg press, gastrocnemio seated and mat. The sample was composed of 08 sedentary individuals, from 20 to 30 years of age and without any impediment in the accomplishment of physical activities, being 04 of the feminine sex and 04 of the masculine sex. The it collects of the data was divided into two moments. At the first moment it was applied IPAQ and PAR-Q questionnaires, collected the cardiac frequency of rest and load recognition to be used in the training of force and at the second moment the circuit with the monitoring of the cardiac frequency was made, having total duration of 28'35 ". In the results we got the ratio of 01 to each 04 women and/or men who had remained above of 55% of the training session inside of the individual white zone, being thus the minority of the sample. We concluded that the control of the training variables, even if the program is systemized, bringing more coherent and trustworth results with the literature regarding training lapsing.
Keywords: physical activity; aerobic exercises; cardiac frequency